Analysis of Branded Cattle Feed Industry in Saurashtra Region: A Case Study of Rajkot, Junagadh, and Amreli Districts, India - , Mukeshkumar J. Balas, Prajapati Mahesh R. (Archives of Current Research International, 2024)
This study investigates the branded cattle feed industry in the Saurashtra region of Gujarat, specifically in Rajkot, Junagadh and Amreli districts. The research aims to analyze the competitive landscape and identify the problems faced by cattle feed dealers. Research was carried out using a descriptive research design and non-probability purposive sampling, 224 cattle feed dealers were surveyed across 32 talukas from the selected districts. The analysis covered compound cattle feed (CCF), cotton seed cake cattle feed, and maize seed cake cattle feed comparing various brands based on price, profit margin, and selling quantities. Key findings reveal significant variations in prices, profit margins and selling quantities among different brands and districts. For Compound Cattle Feed (CCF), Rajmoti 8000 was the top-selling brand in Amreli, Rajvadi 8000 in Junagadh and Doodh Shakti in Rajkot. In the cotton seed cake segment, Krishna Oil Mill in Junagadh, Khedut Oil Industry in Amreli and Ramkrushna Industry in Rajkot had the highest monthly sales. Using Garrett’s ranking method, the study identified key strengths of top-selling brands based on parameters such as product quality, promotional activities, sales quantity, credit period and brand image. Doodh Shakti’s strength in Rajkot was its sales quantity and promotional activities while Rajvadi 8000 in Junagadh focused on product quality and brand image. In Amreli Rajmoti 8000 emphasized product quality and promotional activities. Within the cattle feed industry, Problems faced by dealers included maintaining product quality, establishing appropriate pricing, accessing credit and a lack of storage facilities in which product quality is the most critical issue. This study provides valuable insights for farmers, dealers and businesses of the cattle feed industry in the Saurashtra region.